Modernization, self-control and lethal violence. The long-term dynamics of European homicide rates in theoretical perspective - Eisner, Manuel (The British journal of criminology, 2001)
The present paper examines secular trends of homicide rates by means of a systematic re-analysis of all available quantitative studies on pre-modern homicide. The results confirm, first, that homicide rates have declined in Europe over several centuries. Second, the empirical evidence shows, that unequivocal decline began in the early seventeenth century. Third, the data indicate that the secular decline begins with the pioneers of the modernization process, England and Holland, and slowly encompasses further regions. These findings corroborate much of the civilizing process framework proposed by Norbert Elias. Yet, the diffusion of self-control was sustained not only by compliance to the state monopoly of power but by a variety of disciplining institutional arrangements. This includes, for example, the early expansion of schools, particularly in Northern Europe, the rise of religious reform movements, and the organization of work in manufacturing. Second, while social disciplining certainly is the central feature of the early modern period, it also served to push forward the rise of the specifically modern individualism that Durkheim sees as the cause of the decline of individual-level violence